Manajemen Keputusan Berisiko - M. Munir Achyar; Refaldy Barry Sahputra; Wildan Rizki F; Indra Maulana; Senggi Pangkio; Puji Kurniasari; Wisnu Satria (LABATILA: Jurnal Ilmu Ekonomi Islam, 2021)
An organization or company cannot be separated from the activity of managing risk. Management must decide how to manage economic resources according to the goals of the organization or company. Risk is a hazard or a threat or possibility of an action or event that has an impact which is contrary to the objectives to be achieved. The method used in this research is descriptive analysis with a qualitative approach where this approach describes research on a subject. Sources of data are secondary data obtained through library research in the form of journals, news articles, and books related to research. The data that has been collected will be classified, then verified whether it is in accordance with the research and then analyzed. The results of the study found that a leader must be brave in making decisions because the determination of decision making greatly affects the achievement of organizational goals and also an action to solve problems.